Another me - MacPhail, Catherine 1946-2021 (Bloomsbury, 2011)
"Fay cannot understand what is happening. She is being followed by someone who looks and talks just like her. Even Fay's best friends cannot tell the difference between her and the 'other' Fay. The only person who really listens to Fay is Drew, good-looking and interested in all things spooky. Can Drew help her before the other Fay takes over for ever?" Klappentext
Originally published: 2003
Keywords: False personation / Fiction; False personation; Young adult fiction; Fiction; Thrillers (Fiction); Young adult works; Fiktionale Darstellung; Kinderbuch